‘Way Too White’: Navigating Our Colonial Legacies Through Critical Discussions on Positionality and Power Dynamics With Palestinian Feminist Scholars - Federica Cavazzoni; Guido Veronese; Mona Ameen Nofal; Cindy Sousa; Kathleen Fincham; Nadera Shalhoub-Kevorkian (Journal of Social and Political Psychology)
Particularly in recent years, interest in decolonizing knowledge production is increasing considerably. Debates have raised within various academic disciplines on the role of the researcher's positionality in the research and knowledge production process. Reflexivity and positionality have become keywords within feminist and anti-oppressive research, forcing scholars to confront a critical analysis of how knowledge is shaped and influenced by their positionality (in terms of race, class, gender, sexuality and other axes of social difference). Yet, there still strongly prevails the dominance of knowledge production by Western countries, which often maintain racialized representations of the populations of the rest of the world with them. Hence, in the present exploratory study we focused on practices of reflexivity during the research process as fundamental steps to support efforts to decolonize knowledge through examining researchers’ positionality, power and privilege in relation to their research settings, contents and participants. Through 21 research-discussion with feminist activists and researchers who had experience with cross-cultural and anti-oppressive research and anti-oppressive research methodologies, we delved into a reflective research process. The present study offers critical and methodological insights on how to protect one's research, and research process, from turning into relations of oppression, domination or control, especially when doing fieldwork in a cross-cultural setting.